Biomass and bioenergy : applications - Jawaid, Mohammad; Rashid, Umer; Hakeem, Khalid Rehman (Springer International Publishing, 2014)
The current book is the second volume of the "Biomass and Bioenergy" series, specifically written to offer new and updated materials related to the applications of biomass and bioenergy. Unique topics include non-wood renewable materials (oil palm, bamboo, rattan, bagasse, and kenaf); upgrading of oil palm as added product (a long identified sustainable source of renewable energy); biodiesel synthesis using transesterification of triglycerides and application of single-step process for biodiesel synthesis from microalgae; electrochemically active biofilms for microbial fuel cells, nanomaterial synthesis, bioremediation and bio-hydrogen production; microalgal biomass as a source of renewable energy; a critical analysis of the current situation and future needs for lignocellulosic biomass; utilization of sawmill by-product for making cellulose and its valuable derivatives; valorization of oil palm biomass in relation to biorefinery approach; polylactic acid-based kenaf biomass synthesis; chemical functionalization of natural cellulosic fibers for green polymer composites applications; recent applications of kapok fiber; abaca fiber as a renewable bio-resource for industrial uses and other applications in environmental protection; recent advances in nanofibrillated cellulose extraction; termites from pest to biopolymer derivatives extractor with special emphasis on termite lignocellulolytic system; and last but not least, applications of biomass derived catalyst. We hope this book will serve as a comprehensive primer for individuals who are interested in learning about the vast potentials of tropical biomass.